MATHEMATICAL APPLICATIONS OF THE INDUCTION METHOD IN THE THEORY OF ABSTRACT STATIONARY EQUATIONS - Kulikov, I. V. (Matematichki Bilten, 1992)
We study abstract systems of stationary inequalities of the following type: \[ _1≤ j≤ m a_ijK_τ_ij (x_j)≤ N_i, 1≤ i≤ t, \] where \(m,t,N_i\) (\(1≤ i≤ t\)), \(a_ij\) (\(1≤ i≤ t, 1≤ j≤ m\)) are the elements of the set \(Z_+\) - the set of natural numbers. In this article we formulate and prove theorems about the solutions of an abstract stationary equation \(K_η(x)=r\), \(rZ_+\), and observe [7] estimates for the number of solutions of (1).